INCOME AND LOSSES FROM FINANCIAL ACTIVITIES OF ENSURING FINANCIAL STABILITY OF BUSINESS ENTERPRISES - Odinabonu Otajon qizi, Ileshova (Research Parks Publishers, 2023)
Financial from activity received result enterprise activity of the result separately account as consists of and analysis will be done. Financial from activity received benefit and damages of the enterprise fund market, finance in the market from the activity coming the results. Financial from activity removable revenues the product work and services at the cost of to be entered costs, product work and services work take out and sell expenses composition and financial of results formation order about To the statute suitable is composed. Financial from activity received of income of enterprises total account benefit contained weight last in years one until grow up in Bermuda. Financial from activity received revenues to the the following. For example, another enterprises in the activity characteristic from participation received income, currency of funds course from change received income , other to enterprises , branches , associates to businesses given debts on this received income , interest on this received and is tied up income , shares on this received dividends and amount .